Improved body composition decreases the fat content in non-alcoholic fatty liver disease, a meta-analysis and systematic review of longitudinal studies - Mátis, Dóra; Hegyi, Péter; Teutsch, Brigitta; Tornai, Tamás; Erőss, Bálint; Pár, Gabriella; Váncsa, Szilárd (Frontiers in Medicine, 2023)
Background Based on cross-sectional studies, there is a link between body composition parameters and steatosis in non-alcoholic fatty liver disease (NAFLD). However, whether long-term changes in different body composition parameters will result in NAFLD resolution is unclear. Therefore, we aimed to summarize the literature on longitudinal studies evaluating the association between NAFLD resolution and body composition change. Methods Based on the recommendations of the Cochrane Handbook, we performed a systematic search on September 26th, 2021, in three databases: Embase, MEDLINE (via PubMed), and Cochrane Central Register of Controlled Trials (CENTRAL). Eligible studies reported on patients with NAFLD (liver fat >5%) and examined the correlation between body composition improvement and decrease in steatosis. We did not have pre-defined body composition or steatosis measurement criteria. Next, we calculated pooled correlation coefficient (r) with a 95% confidence interval (CI). Furthermore, we narratively summarized articles with other statistical methods. Results We included 15 studies in our narrative review and five in our quantitative synthesis. Based on two studies with 85 patients, we found a pooled correlation coefficient of r = 0.49 (CI: 0.22–0.69, Spearman's correlation) between the change of visceral adipose tissue and liver steatosis. Similarly, based on three studies with 175 patients, the correlation was r = 0.33 (CI: 0.19–0.46, Pearson's correlation). On the other hand, based on two studies with 163 patients, the correlation between subcutaneous adipose tissue change and liver steatosis change was r = 0.42 (CI: 0.29–0.54, Pearson's correlation). Furthermore, based on the studies in the narrative synthesis, body composition improvement was associated with steatosis resolution. Conclusions Based on the included studies, body composition improvement may be associated with a decrease in liver fat content in NAFLD. Systematic review registration Identifier: CRD42021278584.